Verbal and physical behaviors among football fans: A study of Malaysia football fans at the stadium - Yusoff, Nur Hafizah (School of Social Sciences, 2015)
This study focused on behaviors which are combining of verbal and physical behaviors among football fans at the stadium. Football is one of the popular sports in the world. Fans now days, watching football not just because they want to fill their leisure time, but for them football is being a part of their life. There are many types of fans coming to the stadium and some of the fans are really fanatic with the team. Verbal and physical behaviors among football fans is not a new issue in Malaysia but lately, this phenomena keep repeating happen and it show that the fans never learn from the mistakes. A survey was done to obtain the data. Numbers of 600 football fans from state of Kelantan, Perak, Selangor and Johor were chosen to be respondents. These fourth teams known because they have huge fans and their fans always break the rules and the team also keep being punished and fined by Football Association of Malaysia (FAM). Respondents around age 18-50 years old were involved within this study (81% male & 19% women). The data showed that various attitudes and behaviour were occur while they were watching